The /rˇ/ phoneme insertion in current Quechua: an explanation from a theory of natural classes - Meneses Tutaya, Norma (2017)
The present study brings a possible explanation of how vibrant multiple prepalatal /ř/ is a «natural» segment in consonantal inventory of current Quechua despite its evident derivation from the contact with Spanish. In other words, the phoneme /ř/ has been incorporated into the phonological system of some dialects of Quechua and it is in process of expansion to all dialects, due mainly to its correspondance to a «natural» slot within the Quechua system rather than a merely loan explanation or an interference of the Andean Spanish. In any case, without neglecting any of the given explanations, I propose that the determinant factor is intrinsic to the phonological system of Quechua from the point of view of a natural classes theory. Because of this theory, Quechua consonantal system is organized into natural classes, where [+cons, +cor] class is nuclear. Within this natural class there is an opposition between two subclasses: [+cons, +cor, +ant] / [+cons, +cor, +post]. The presence of the multiple retroreflex vibrant would be explained by their relocation in the second subclass where it fullfills an empty cell.